An aminonaphthalimide-putrescine conjugate as fluorescent probe for cucurbituril host-guest complexes - Carvalho, Cátia Parente (2015)
A fluorophore-anchor dye based on the 4-amino-1,8-naphthalimide chromophore was designed and characterised with respect to its ability of forming supramolecular hostguest complexes with cucurbit[6]uril (CB6) and cucurbit[7]uril (CB7) hosts. It was found that CB6 encapsulates the anchor of the dye with a high binding constant [K = (1.11.4) X 107 M- 1], which was independent of acidic or neutral pH conditions. The 1:1 binding was accompanied by fluorescence quenching (ca. 20%) and a bathochromic shift (?? = +22 nm) of the charge-transfer absorption band of the dye. This is indicative of the occurrence of hydrogen bonding between a carbonyl-lined host portal and the aromatic NH group of the guest dye. In comparison, CB7 encapsulated the dye much less efficiently (K = 4.8 X 104 M- 1) and showed a significant fluorescence enhancement (Ff = 0.15 versus 0.52 for free and CB7-complexed dye at pH 4, respectively). The occurrence of hydrogen bonding with the aromatic NH was much less evident for CB7 as judged by the only minor bathochromic shift (?? = +4 nm) of the charge-transfer absorption band of the dye. The dyeCB6 assembly has the potential for the detection of biogenic amines under physiological pH conditions and at low analyte concentrations.